Penerapan Arsitektur Ekologi Sebagai Acuan Pengembangan Kawasan Wisata Pantai di Kabupaten Sinjai - Irma Rahayu; Muhammad Attar; Aras, Muh. Mursyidin (The Department of Architecture, Faculty of Science and Technology, Alauddin Islamic University of Makassar, 2022)
Abstract_ Indonesia has abundant natural resources in the form of oceans, sun and beaches. This wealth, if managed properly and correctly, can provide large foreign exchange for the country. One way to use it is to make the area a tourist destination. Areas that are endowed with exotic natural resources are expected to make a major contribution in providing a source of income. Moreover, with the existence of regional autonomy, a regency/city is required to be able to live independently. The development of the tourism sector has a very strategic role in supporting national and regional economic development, because it is a source of foreign exchange earners capable of absorbing labor and encouraging the development of domestic investment. Architectural ecology is the basic thing that is used as a benchmark for the development of coastal tourism areas with principles that prioritize environmental aspects as the main consideration in the process and product design.